Adaptation and validation of an adverse drug reaction preventability score for bleeding due to vitamin K antagonists. Issue 39 (September 2016) - Liabeuf, Sophie; Masmoudi, Kamel; Scailteux, Lucie-Marie; Moragny, Julien; Masson, Henri; Brnet-Dufour, Valérie; Andrejak, Michel; Gras-Champel, Valérie
Abstract : Abstract: Although drug therapy is inherently associated with the risk of adverse drug reactions (ADRs), some of these events are preventable. The estimated proportion of preventable ADRs varies from one study or clinical context to another. Bleeding caused by antithrombotic agents (and particularly vitamin K antagonists, VKAs) constitutes one of the most frequent causes of ADR-related hospitalization. Hence, the objective of the present study was to adapt and validate an ADR preventability score for bleeding due to VKAs and evaluate the preventability of bleeding in 906 consecutive hospitalized, VKA-treated adult patients with a risk of major bleeding (defined as an international normalized ratio ≥5) over a 2-year period. A specific preventability scale for VKA-associated bleeding was developed by adapting a published tool. Overall, 241 of the 906 patients in the study experienced at least 1 VKA-associated bleeding event. The scale's reliability was tested by 2 different evaluators. The inter-rater reliability (evaluated by calculation of Cohen's kappa) ranged from "good" to "excellent." Lastly, the validated scale was used to assess the preventability of the VKA-associated bleeding. We estimated that bleeding was preventable or potentially preventable in 109 of the 241 affected patients (45.2%). We have developed a useful, reliable tool for evaluating the preventability of VKA-associated bleeding. Application of the scale in a prospective study revealed that a high proportion of VKA-associated bleeding events in hospitalized, at-risk adult patients were preventable or potentially preventable.